Polarization of membrane associated proteins in the choroid plexus epithelium from normal and slc4a10 knockout mice - Christensen, Inga B.; Gyldenholm, Tua; Damkier, Helle H.; Praetorius, Jeppe (Frontiers in Physiology, 2013)
The choroid plexus epithelium (CPE) has served as a model-epithelium for cell polarization and transport studies and plays a crucial role for cerebrospinal fluid (CSF) production. The normal luminal membrane expression of Na+,K+-ATPase, aquaporin-1 and Na+/H+ exchanger 1 in the choroid plexus is severely affected by deletion of the slc4a10 gene that encodes the bicarbonate transporting protein Ncbe/NBCn2. The causes for these deviations from normal epithelial polarization and redistribution following specific gene knockout are unknown, but may be significant for basic epithelial cell biology. Therefore, a more comprehensive analysis of cell polarization in the choroid plexus is warranted. We find that the cytoskeleton in the choroid plexus contains αI-, αII-, βI-, and βII-spectrin isoforms along with the anchoring protein ankyrin-3, most of which are mainly localized in the luminal membrane domain. Furthermore, we find α-adducin localized near the plasma membranes globally, but with only faint expression in the luminal membrane domain. In slc4a10 knockout mice, the abundance of β1 Na+,K+-ATPase subunits in the luminal membrane is markedly reduced. Anion exchanger 2 abundance is increased in slc4a10 knockout and its anchor protein, α-adducin is almost exclusively found near the basolateral domain. The αI- and βI-spectrin abundances are also decreased in the slc4a10 knockout, where the basolateral domain expression of αI-spectrin is exchanged for a strictly luminal domain localization. E-cadherin expression is unchanged in the slc4a10 knockout, while small decreases in abundance are observed for its probable adaptor proteins, the catenins. Interestingly, the abundance of the tight junction protein claudin-2 is significantly reduced in the slc4a10 knockouts, which may critically affect paracellular transport in this epithelium. The observations allow the generation of new hypotheses on basic cell biological paradigms that can be tested experimentally in future studies.